Electronic money (e-money) in maqashid al-sharia perspective - Afif Muamar; Ari Salman Alparisi (Journal of Islamic Economics Lariba, 2017)
Electronic money emerges as micro payment instrument in which it enables faster, easier, safer and more efficient payment process. Even though it offers many advantages, its appropriateness to maqasid al-sharia needs to be further disucssed. Thus, it is very imporant to judge whether e-money has been in line with Islamic values or not. The method used in this research was qualitative method in which literature studies were performed. The result generally suggested that e-money had not violated maqasid al-sharia. This congruity was taken as it did not contravene the principles of wealth management and usefulness in Islam. However, unregistered e-money was judged not in line with maqasid al-sharia because it might create disadvantages when it was stolen or lost. It was due to the fact that unregistered e-money was not equipped with password. Thus, the use of unregistered e-money should be better avoided.